Morpho‐taxonomic identification of algal diversity of district Lahore based on light microscopic techniques. Issue 11 (12th May 2021) - Mukhtar, Anser; Jaffer, Mehwish; Shaheen, Shabnum; Ullah, Nadeem; Rehman, Shafiq ur
Abstract: Total 23 algal species belonging to 14 genera were reported from different sites of district Lahore. They were collected from freshwater of some areas of Lahore city during October 2017 to March 2018. All were taxonomically investigated up to specie level using light microscopy (LM). Following species were identified: Achanthes hungarica (Grunow) Grunow in Cleve et Grunow 1880, Achnanthes minutissima (Kützing) Cleve, Anabaena affinis Lemmermann, Aphanothece endophytica G.M. Smith, Aphanothece nidulans P. Richter, Calothrix fusca (Kützing) Bornet & Flahault, Chroococcus limenticus var. distans G.M. Smith, Chroococcus minor (Kützing) Lemmermann, Cyclotella operculata (C.A. Agardh) Brebisson, Cymbella ehrengbergii Kützing, Cymbella turgida, Lyngbya arboricola Bruhlet Bruh, Lyngbya tylorii Drouet & Strickland, Navicula confervacea (Kützing) Grun. var. confervacea, Navicula knsnesis Meister, Oedogonium behemicum Hirn, Oscillatoria amoena (Kützing) Gomont, Oscillatoria amphibia C. Agardh ex Gomont, Oscillatoria subbrevis Schmidle, Pinuularia interrupta W. Smith, Spirulina subsala (Oersted) ex Gomont, Ulothrix aequalis Kützing, Ulothrix tenuissima Kützing. Abstract : The research was planned to study: the diversity of algal species of various selected areas of Lahore light microscopy was used to determine the morphological and anatomical characters It was concluded that species varies as altitude varies and their anatomical changes also been observed using LM.